Inspection of pathological manifestations and map of damage on facades: case study in "Block C" of the polytechnic school of Pernambuco - Alves, Lúcia Selene Bezerra; de Moura Junior, Jose Maria; Póvoas, Yêda Vieira; Campelo, Gabriela de Figueiredo Carneiro; Rodrigues, José Matheus de Castro (Seven Editora, 2023)
The Polytechnic School of Pernambuco, located at Rua Benfica, 455, in Bairro da Madalena, Recife - PE, has several blocks and completed 110 years this year (2022). It is possible to verify pathological manifestations throughout the university. Because of this, this research aims to perform an inspection to evaluate the current situation of the pathological manifestations found in the facades of "block C" and to elaborate a map of its damage. A literature review and case study were elaborated on the subject in question and related issues. The case study was done through the visual inspection methodology and has preliminary inspection, consisting of the collection of data related to structure and environment, an inspection of facades through surveys, with photographic records and preliminary diagnoses. Measurements were made to design the facades with software aid. Thus, the analysis was finalized, starting the elaboration of the data map, in addition to identifying the possible causes of the damage. That said, the identification of different pathological manifestations, on the façade of the studied block, will be presented. It is also expected that this project will contribute to the planning of a maintenance plan for "block C". With this, it is expected to contribute to the maintenance and restoration services of the studied construction. DOI: https://doi.org/10.56238/methofocusinterv1-056